Lassa fever: another threat from West Africa - Brosh-Nissimov, Tal (Disaster Mil Med, 2016)
Lassa fever, a zoonotic viral infection, is endemic in West Africa. The disease causes annual wide spread morbidity and mortality in Africa, and can be imported by travelers. Possible importation of Lassa fever and the potential for the use of Lassa virus as an agent of bioterrorism mandate clinicians in Israel and other countries to be vigilant and familiar with the basic characteristics of this disease. The article reviews the basis of this infection and the clinical management of patients with Lassa fever. Special emphasis is given to antiviral treatment and infection control.